TINJAUAN MOTIVASI BELAJAR SISWA PADA KELUARGA YANG MENGALAMI PERCERAIAN (BROKEN HOME) DI SEKOLAH DASAR NEGERI JEMUR WONOSARI 1 - Erika Nurkumalarini (Universitas Negeri Medan, 2020)
The purpose of this study was to determine student learning motivation in families experiencing divorce (broken home) and to find out the strategies of teachers in (broken home) at the school.From the data and data sources which doing in wonocolo, surabaya city use subject in primary school children of 4 children.Data collection techniques in this research using observation techniques, interviews, documentation until analysis technique, and in data this research method which using qualitative-descriptions.The results of this study indicate that children who have incomplete families, have broken home families, subjects still lack high motivation to learn. In addition, the strategies carried out at SDN Jemur Wonosari 1 Surabaya show that teachers teach various strategies and learning methods such as lecture methods, discussions, questions and answers, and assignments so that students are motivated to participate in learning and are active and affective so that students are not bored and are bored in learning process takes place.Keywords: Learning, Motivation, Broken Home